When Womanhood Matters: Sex Essentialization and Pedagogical Dissonance in Buddhist Discourse - Dhammadinnā, Bhikkhunī (Religions of South Asia, 2018)
This article further articulates Sponberg’s (1992) seminal identification of four distinct attitudes toward women and the feminine in Buddhism, by including a sub-typology of ‘essentialist misogyny’. Textual and institutional voices in the Buddhist traditions are traced that testify to a process of essentialization of the female sex or gender that is first constructed as an entity, ‘womanhood’, and then devalued. This trend is already documented in the early Buddhist texts, where it stands in contrast to the soteriologically normative nonessentialized view of femininity. The discourse develops with misogynist positions taken in medieval Theravada works. It is further continued, albeit under an opposite agenda, that of the ‘Sacred Feminine’, in contemporary Western Buddhism. Such contemporary instances of an essentialized feminine exemplify how doctrinal and religio-historical tensions are renegotiated leading to the emergence of new incarnations of the Theravada, and Buddhist in general, scriptural canon, which in turn overwrite previously emerged ‘practical canons’.